Implementasi Akad Dalam Perbankan Syariah Khususnya Jenis pembukaan tabungan di Bsi Cabang Cilacap diponegoro: Implementasi Akad Dalam Perbankan Syariah Khususnya Jenis pembukaan tabungan di Bsi Cabang Cilacap diponegoro - Pratama, Indah riski; S, Umi Ma’rifah; Latifah, Anisatul (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This research examines how Islamic contract principles (akad) are applied in Islamic banking, specifically looking at the types of contracts used when opening Islamic savings accounts at the Bank Syariah Indonesia, Cilacap Diponegoro Branch. The goal of this study is to evaluate the application of Islamic legal concepts, like wadi’ah and mudharabah, in banking processes and to determine their adherence to Sharia compliance standards. A qualitative descriptive method was utilized for data collection through interviews, documentation, and observations conducted at the branch. Results indicate that the application of akad in Islamic savings complies with the rules established by the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) as well as the internal guidelines of Bank Syariah Indonesia. The research concludes that the practical use of akad in the Islamic savings accounts at the Cilacap Diponegoro branch aligns with Sharia principles, promoting fairness, transparency, and mutual advantages for both the bank and its clients.